2008
DOI: 10.1519/jsc.0b013e31816d5eda
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Countermovement Jump Performance and Multijoint Isometric and Dynamic Tests of Strength

Abstract: The purpose of this investigation was to determine the relationship between countermovement vertical jump (CMJ) performance and various methods used to assess isometric and dynamic multijoint strength. Twelve NCAA Division I-AA male football and track and field athletes (age, 19.83 +/- 1.40 years; height, 179.10 +/- 4.56 cm; mass, 90.08 +/- 14.81 kg; percentage of body fat, 11.85 +/- 5.47%) participated in 2 testing sessions. The first session involved 1 repetition maximum (1RM) (kg) testing in the squat and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
234
6
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(267 citation statements)
references
References 26 publications
(88 reference statements)
19
234
6
8
Order By: Relevance
“…The inclusion of peak power at the knee and ankle joints in the overall regression model supports previous claims that CMJ performance is positively associated with lower-limb power (Ashley & Weiss, 1994;Nuzzo et al, 2008;Sheppard et al, 2008;Vanezis & Lees, 2005). The work-energy-power relationship makes it inevitable that greater joint powers result in more positive work done and so greater total body kinetic energy and mass centre vertical velocities at take-off.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The inclusion of peak power at the knee and ankle joints in the overall regression model supports previous claims that CMJ performance is positively associated with lower-limb power (Ashley & Weiss, 1994;Nuzzo et al, 2008;Sheppard et al, 2008;Vanezis & Lees, 2005). The work-energy-power relationship makes it inevitable that greater joint powers result in more positive work done and so greater total body kinetic energy and mass centre vertical velocities at take-off.…”
Section: Discussionsupporting
confidence: 76%
“…Research has shown positive relationships between lower-limb strength and power measures and CMJ performance (Ashley & Weiss, 1994;Nuzzo, McBride, Cormie, & McCaulley, 2008;Sheppard et al, 2008;Wisløff, Castagna, Helgerud, Jones, & Hoff, 2004). However, further research is needed to explain quantitatively the relative contributions of kinetic and kinematic variables to this movement.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability scores found for CMJ are comparable with values found for maximal voluntary contractions (Raeder et al, 2016). Additionally, the CMJ performance is strongly correlated to maximal strength and power in multijoint exercises of the lower limbs (Nuzzo et al, 2008).…”
Section: Countermovement Jump (Cmj)supporting
confidence: 70%
“…Progression phase 2 consisted of 12 weeks of heavy resistance training, with two training sessions a week, focusing on maximum strength and performance mainly in the multiple-joint exercises. Multiple-joint exercises require rapid force production and have been widely used for strength and power training 20,33 . Because vertical jump capacity (a multiple-joint movement) is critical for success in volleyball, multiple-joint exercises were included in the present study, as well as ordinary explosive strength exercises, such as the barbell jump squat.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that tests using free weights reflect the functional strength in sports 20,33 . For example, maximum squat strength has been shown to have a strong relationship with vertical jump height 20 .…”
Section: Discussionmentioning
confidence: 99%